CRISPR-Cas-mediated unfolded protein response control for enhancing plant stress resistance - Vu, Bich Ngoc; Vu, Tien Van; Yoo, Jae Yong; Nguyen, Ngan Thi; Ko, Ki Seong; Kim, Jae-Yean; Lee, Kyun Oh (Frontiers in Plant Science, 2023)
Plants consistently encounter environmental stresses that negatively affect their growth and development. To mitigate these challenges, plants have developed a range of adaptive strategies, including the unfolded protein response (UPR), which enables them to manage endoplasmic reticulum (ER) stress resulting from various adverse conditions. The CRISPR-Cas system has emerged as a powerful tool for plant biotechnology, with the potential to improve plant tolerance and resistance to biotic and abiotic stresses, as well as enhance crop productivity and quality by targeting specific genes, including those related to the UPR. This review highlights recent advancements in UPR signaling pathways and CRISPR-Cas technology, with a particular focus on the use of CRISPR-Cas in studying plant UPR. We also explore prospective applications of CRISPR-Cas in engineering UPR-related genes for crop improvement. The integration of CRISPR-Cas technology into plant biotechnology holds the promise to revolutionize agriculture by producing crops with enhanced resistance to environmental stresses, increased productivity, and improved quality traits.